KEPEMIMPINAN DIGITAL DALAM PENDIDIKAN BUDAYA INSTITUSI SENI BUDAYA - Azainil; Dwi Nugroho Hidayanto; Muhammad Ramli Buhari; Suprihartini; Novarita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital transformation era presents both challenges and opportunities for art and cultural education institutions in Indonesia. Leadership in this context requires not only administrative and managerial capabilities but also the ability to integrate digital innovation with local cultural values. This study aims to analyze the model of digital leadership in cultural education institutions and to identify effective strategies for maintaining the balance between technological innovation and cultural preservation. This research employed a qualitative approach using a multiple case study design across three Indonesian art and cultural institutions: the Indonesian Institute of the Arts (ISI) Yogyakarta, the Jakarta Institute of the Arts (IKJ), and the Nusantara Academy of Arts and Culture (AKSBN). Data were collected through in-depth interviews, participatory observations, and institutional document analysis. Thematic analysis was conducted using the Miles, Huberman, and Saldaña framework. The findings reveal five key dimensions of culturally rooted digital leadership: (1) digital vision grounded in local cultural values; (2) pedagogical innovation in art education through technology; (3) intercultural collaboration and global networking; (4) strengthening institutional digital identity; and (5) ethical and spiritual awareness in digital transformation processes. The proposed Cultural–Digital Leadership Model emphasizes that the success of digital transformation in art institutions is not measured by the level of technology adoption, but by how effectively technology reinforces cultural identity, ethics, and national character. This study contributes theoretically to the development of a culturally grounded educational leadership model and practically provides guidance for policymakers and institutional leaders in designing sustainable and culturally conscious digital transformation strategies for art and cultural education.